從工具示能性與關係行動主體之觀點 探討偏鄉教育系統賦能策略之研究 Investigating the Construction of Empowerment Action Models in Remote Educational Systems Through the Lenses of Tool Affordance and Relational Agency - 陳佩英 Peiying Chen; 洪琴雯 Chin-Wen Hung (Journal of Research in Education Sciences)
偏鄉教育問題盤根錯節，需要找出問題解決的創新策略。本研究與個案縣市T合作，以「示能性」（affordance）和「關係行動主體」（relational agency）的觀點切入，探討T縣以培養在地人才解決在地教育問題的系統賦能策略之發展過程及其意義。研究者以T縣學校為場域，瞭解其如何培力與組織在地人才，轉化外部政策與在地教育發展需求，並整合在地資源，以啟動在地行動策略。研究為期一年半，經由實地觀察、深度訪談和文件分析等資料蒐集，整理與 分析T縣核心團隊如何經由參與培力增能方案，使用與改造工具，作為專業學習的技術提升、團隊建立的關係連結、跨界協力的資源整合之系統賦能策略。研究發現，核心團隊開發的工具群組具備「可行」與「實用」的示能性，不僅能促進關係行動主體的發展，也能激發團隊成員的本能知覺、個體與集體的認知行為與深層反思，在集體探詢的迭代創新過程，找到培養在地人才解決在地教育問題的可行路徑。 Motivation and Purpose Literature relating to rural education has been accumulated, with most problems falling into the “known” category. However, finding innovative practices to solve these problems still requires seeking alternative pathways to identify possibilities for structural and cultural transformation. The study employed a culturally responsive inquiry strategy to establish local “observing, knowing, acting, and reflecting” action knowledge and accumulate second-order social capital for systemic change (Leithwood, 1994; Thornton et al., 2012). Taking T County as the main field, this study began by problematizing rural education and adopted a system empowerment perspective that responded to local needs. The researchers collaborated with frontline educators to co-develop a revitalization model suitable for rural education through talent cultivation programs, diverse professional resource matching, and an inquiry cycle of “design, implementation, feedback, revision, and deepening.” The research questions guiding this study were as follows: 1. How can rural areas introduce key resources, establish relational agency, cultivate local talent, and develop system empowerment strategies to solve local educational problems? 2. How can local educational problems be addressed through the local practices of relational agency, by developing and utilizing tool sets that respond to local issues, and achieving system empowerment effects? Literature Review This study employed the concepts of affordance and relational agency as the main analytical frameworks. Affordance refers to the ways in which tools induce users’ behaviors, cognitive actions, and reflections. However, users’ behaviors can also exceed the original intentions of tool designers; that is, the flexible use of tools depends on users’ cognition of tool properties, the use of the tool’s own prompts, and the judgment of problems or environments to modify the use or function of the tool to achieve goals (Hammond, 2010). Relational agency refers to the process by which groups of actors promote mutual understanding and transform individual cognition and interpretation through dialogue and negotiation, fostering connections in pursuit of common goals and tasks, enhancing collective action, and ultimately solving problems and achieving objectives. The concept of relational agency is closely related to the development of professional capital in teacher PLCs. Through the accumulation of human capital and social capital embedded in relational agency, and the process of collective inquiry and reflection among teachers, an effective “decisional capital” of teaching experts is formed, along with the accumulation of “a shared repertoire of practice.” This study thereby utilized relational agency to describe how local problems could be transformed into practical goals through the co-learning and co-action of actors, while tool affordances served as the mediating effect and evidence of relational agents’ goal-oriented practices, demonstrating the trajectory of system empowerment and organizational change. Method This participatory case study was conducted in T County from November 2019 to May 2021. In addition to the researchers’ existing partnership with T County, the case was selected because it is a typical rural county, with more than 70% of its primary and secondary schools classified as remote area schools. The study primarily collected data through participatory observation and semi-structured interviews and used NVivo software as a qualitative data analysis tool. A total of 66 field observation records and 17 interview data were collected, with 5 in-depth interviews and 11 observation records used in this paper. Results Problematization of the Rural Education Context and Formation of Strategic Actions Long-standing views among T County educators regarding the local educational environment included insufficient teacher quality and quantity, unstable administrative leadership, and weak student family support. However, these existing disadvantages might be transformed by means of implementing the new National Curriculum Guidelines in 2019. In 2019, inspired individuals collaborated with the research team to establish a “core teacher team,” with the primary goal of effectively empowering local educational talent. The team, guided and accompanied by coach Chin, aimed to build a mutually supportive team that transformed thinking and engaged in collective inquiry learning while co-developing techniques and tools for interdisciplinary curriculum design. The team members progressed from initial individual learning to developing organizational practice action plans. The in-school empowerment workshops were designed to assist the participant schools in developing school-based curricula. Recruiting and assigning cooperative partners and tool creation were important to boost the capacity building, which ensured that the in-school empowerment workshops aligned with action goals. Tool-Induced Team Learning and Action The second part uses three tools introduced by Chin - interdisciplinary curriculum design tools, wave analysis, and an action planning toolset– to illustrate how tool affordance triggered inquiry and its effects within the team. The interdisciplinary curriculum design tool module aimed to guide collective discussions and design competence-oriented curricula that integrated students’ authentic life experiences. “Wave analysis” was a visual tool that used the pictorial images of waves to elicit deep dialogue within the team using intuitive perceptions, information interpretation of events, and reflection. The tool module for mobilizing group learning and action consisted of six toolsets. These goal-oriented and in-depth inquiry tools elicited team members’ recognition of the overall plan and its details, leading to multi-faceted views and assessments of the current situation. Finally, in the process of providing school empowerment workshops, the team developed tools such as interview questionnaires, curriculum planning forms, coach self-assessment forms, and school momentum assessment forms to respond to the needs raised by schools. Discussion and Suggestions Constructing and Cultivating a Collaborative Culture of Relational Agency Was Essential for Solving Structural Problems in Rural Areas In this study, a team composed of diverse professionals with high momentum could sustain and transform members’ professional learning. The input of appropriate external professional resources could develop reciprocal and trusting social capital. Obtaining concrete support from the governing authority was crucial for stabilizing the development of talent cultivation programs. The Affordance Tools Co-created by the Team Could Achieve the Effects of Technical Enhancement, Relational Connection, and Resource Integration Through dialogue and practice, participants realized that improving teaching did not stem from changes in operational techniques, but rather from making curriculum development filled with “warmth” (caring for participants and the environment) and “plasticity” (feasible flexibility). The process allowed the team to feel “using the tool” rather than “being used (limited) by the tool,” and even transforming the tool. This was the practical and creative value of tools and the key cognition for the team’s continuous professional learning. Continuous Inquiry Cycles Were an Effective Way to Construct Rural Education System Empowerment Due to the Complex and Rapidly Changing Nature of Rural Education Systems Learning from feedback in practice and ongoing discussion was particularly important. Specifically, this study included four key steps: “design, implementation, feedback and revision, and deepening.” In the design stage, the three external tools mentioned above were used to establish team consensus, lay the foundation for professional knowledge, and design program processes. In the implementation stage, in-school empowerment workshops were held. After entering the school, discussions and mutual feedback were conducted, and the results of the team’s joint discussions were used as a reference for revision, allowing each group to revise the process design of each school’s in-school service. Finally, the deepening stage was an extension of the inquiry cycle, continuously improving the efficiency and responsiveness of the model through re-entry into schools and further developing new tools or processes based on needs. Conclusion In conclusion, the complex problems embedded in rural schools in terms of structure and system still require policy support. The effective practices of the T County case study provided a dynamic understanding of the contextual and systemic nature of solving rural education issues. The research found that system empowerment began with talent cultivation, followed by establishing a relational agency of mutual trust and shared action, as well as goal consensus. It was crucial in learning to use a common language to develop culturally responsive team learning and curriculum development tools, and continuously shape ongoing professional growth through in-depth dialogue. This might result in reshaping collective cognition and efficacy, and forming a positive cycle of system empowerment and its replicable innovation methods and paths.